Surgical extraction peculiarities of the foreign bodies in weapon wounds of the head in the peace time - Mogila, V. V.; Siomkin, K. V. (Ukrainian Neurosurgical Journal, 2005)
Authors analyzed 204 injured patients with weapon head wounds in the peace time. The majority of wounds were from fowling-pieces, gas-guns, bows, air and selfmade weapons. Projectiles were the shots, pieces of lead, nails, bolts and other. Features of such injuries surgical treatment were analyzed.